The Performance of Red Flares Mg/Sr(NO₃)₂/PVC Compositions Modified with KIO₄ Additives - Elda Pratita; Gunaryo; Minandre Wiratama; Anggaria Maharani; Astrid Blandina; Shella Athaya Miwazuki; Satria Aqilla Widyatama (Indonesian Journal of Chemical Studies, 2026)
This study analyzes the enhancement of red signal flare efficacy for defense applications by formulating Mg/Sr(NO₃)₂/PVC-based pyrotechnics, utilizing various quantities of potassium periodate (KIO₄) as a secondary oxidizer. The addition of KIO₄ is significant as it provides extra oxygen, modifies combus6tion kinetics, raises flame temperature, and enhances the stimulating effect of red-emitting species—mechanisms that together may increase luminous output and stabilize the emitted spectrum band. Performance was assessed by measuring light intensity, dominant wavelength, burn rate, and color purity; spectral and image-based color analyses were performed using ImageJ. Results indicate that formulations containing up to 10% KIO₄ achieve a peak light intensity of 3,173.33 lux, a dominant wavelength of 638.16 nm, a burn rate of 2.01 g/s, and an estimated photon-energy efficiency of 3.54 × 10⁻¹⁹ J, with red emission reaching optimal purity at this composition. Compared to the baseline formulation without KIO₄, KIO₄-containing compositions showed markedly higher intensity and improved spectral stability, faster and more consistent burn behavior, and enhanced color purity—whereas the formulation without KIO₄ exhibited lower luminous output, broader or shifted spectral features, and reduced color stability. The novelty of this work lies in applying potassium periodate as a secondary oxidizer in the Mg/Sr(NO₃)₂/PVC system—an approach that, to our knowledge, has been little explored—and demonstrating its dual benefit for optical performance and combustion behavior. The findings support the recommendation of the 10% KIO₄ formulation as the most effective balance of visual and combustion performance for red signal flares.